2004
DOI: 10.1080/09513590400007242
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gestational diabetes mellitus and pregnancy outcomes in Asian women with polycystic ovary syndrome

Abstract: The aim of this study was to determine the prevalence of gestational diabetes mellitus (GDM) and the pregnancy outcomes in Asian women with polycystic ovary syndrome (PCOS). The retrospective cohort study was performed to compare pregnancy outcomes of 47 pregnancies in 41 PCOS women with 264 pregnancies in 222 women with normal menstruation. Logistic regression was used to assess the risk of PCOS on GDM, hypertensive disorder in pregnancy (HDP) and premature delivery. The mean age of both groups was 31 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 13 publications
3
43
1
Order By: Relevance
“…In the present work, also in accordance with previous findings (Vandermolen et al 2001, Harbone et al 2003, Kazerooni & Dehghan-Kooshkghazi 2003, Weerakiet et al 2004, we demonstrate that the administration of metformin together with DHEA prevented the effect of hyperandrogenization, i.e. the increase of serum E and P levels.…”
Section: Discussionsupporting
confidence: 81%
“…In the present work, also in accordance with previous findings (Vandermolen et al 2001, Harbone et al 2003, Kazerooni & Dehghan-Kooshkghazi 2003, Weerakiet et al 2004, we demonstrate that the administration of metformin together with DHEA prevented the effect of hyperandrogenization, i.e. the increase of serum E and P levels.…”
Section: Discussionsupporting
confidence: 81%
“…Highly related to subfertility and infertility (28), PCO is thus likely to be more common among uniparous compared with biparous women. PCO is associated with increased risks of ovarian cancer (34,35) and preterm birth (36,37) and reduced risk of smallfor-gestational-age birth (38). PCO is also associated with hyperandrogenism and increased IGF-I levels (34), which may also impart effects in the risk of ovarian cancer (17,28).…”
Section: Discussionmentioning
confidence: 99%
“…28 More recently, a South-East Asian study confirmed a similar association between GDM, IR and PCOS among Thai women. 29 It is noteworthy that Ehrmann et al who evaluated the predictive value of race and a family history of T2DM on the metabolic status of a large cohort of women with PCOS found that these factors have a substantial impact on the metabolic and glycaemic status of women. They also evaluated these parameters in women without PCOS and found that a positive family history of T2DM correlated with central obesity and IR, which is mirrored in our study.…”
Section: Discussionmentioning
confidence: 99%